Hello,
8/(x-7)=7/2
==>(x-7)*7=8*2
==>7x-49=16
==>7x=65
==> x =9+2/7
Answser A
Answer:
![x^3-3x^2+2x-\frac{3}{2}](https://tex.z-dn.net/?f=x%5E3-3x%5E2%2B2x-%5Cfrac%7B3%7D%7B2%7D)
Step-by-step explanation:
We can divide polynomials by other polynomials by dividing each term by the denominator. Remember, when we divide a variable by itself, we must change the exponent in our answer according to exponent rules.
![\frac{ (2x^4-6x^3+4x^2-3x)}{2x}=\frac{2x^4}{2x} -\frac{6x^3}{2x} +\frac{4x^2}{2x} -\frac{3x}{2x} =x^3-3x^2+2x-\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%20%282x%5E4-6x%5E3%2B4x%5E2-3x%29%7D%7B2x%7D%3D%5Cfrac%7B2x%5E4%7D%7B2x%7D%20-%5Cfrac%7B6x%5E3%7D%7B2x%7D%20%2B%5Cfrac%7B4x%5E2%7D%7B2x%7D%20-%5Cfrac%7B3x%7D%7B2x%7D%20%3Dx%5E3-3x%5E2%2B2x-%5Cfrac%7B3%7D%7B2%7D)
1. -3/2
2. -1/2
3. 1.3
4. 1 1/2
Answer:
i think so?
Step-by-step explanation:
Answer:
Quadrant 4
Step-by-step explanation:
x > 0 means towards right of the origin
y < 0 means below the origin
So Quadrant 4